Comparison of sevoflurane and propofol in combination with remifentanil on the quality of postoperative recovery in patients undergoing laparoscopic bariatric surgery - Shu, Zhuolin; Lin, Tiancheng; Xu, Dingchen; Zheng, Shuyuan (Frontiers in Medicine, 2024)
Objective: This study aimed to evaluate and compare the effects of sevoflurane + remifentanil (Sev+Rem) and propofol + remifentanil (Pro+Rem) on the postoperative recovery quality of patients undergoing laparoscopic bariatric surgery to determine which anesthesia regimen provides a better overall recovery experience. Methods: Sixty patients were divided into two groups based on the treatments they underwent: Sev+Rem (n = 30) and Pro+Rem (n = 30). The Sev+Rem group received sevoflurane inhalation (0.5%, increasing to 0.5–4%) and remifentanil via target-controlled infusion. The Pro+Rem group received propofol (4–8 mg/(kg·h)) and remifentanil via target-controlled infusion. Anesthesia depth was maintained at a bispectral index of 40–60 in both groups. Perioperative data, hemodynamic parameters, and postoperative recovery quality were assessed. Results: Compared to the Pro+Rem group, the dose of remifentanil in the Sev+Rem group was significantly lower (1693.67 ± 331.75 vs 2959 ± 359.77, P < 0.001), the proportion of patients used norepinephrine was markedly higher [16 (53.33) vs 8 (26.67), P = 0.035], and the time of extubation was earlier (356.33 ± 63.17 vs 400.3 ± 50.11, P = 0.004). The Hemodynamic results showed the HR in the Sev+Rem group was faster than that in the Pro + Rem group at the beginning of surgery and 1 h post-surgery (67.37 ± 4.40 vs 64.33 ± 4.44, P = 0.010; 69.07 ± 4.23 vs 66.40 ± 5.03, P = 0.030). In regard to the assessment of postoperative recovery quality, the emotional state scores in the Sev+Rem group were significantly lower than the Pro+Rem group (36.83 ± 2.79 vs 39.50 ± 4.64, P = 0.009). Conclusion: The two anesthesia modalities (Sev+Rem and Pro+Rem) have their advantages and disadvantages for patients undergoing laparoscopic bariatric surgery and have comparable effects on postoperative recovery quality.